Influence of microcapsule parameters and initiator concentration on the self-healing capacity of resin-based dental composites. Issue 3 (March 2021) - Ning, K.; Loomans, B.; Yeung, C.; Li, J.; Yang, F.; Leeuwenburgh, S.
Graphical abstract: Highlights: Relationship between self-healing capacity and initiator concentration. Relationship between self-healing capacity and microcapsule size and concentration. Implementation of microcapsule-based self-healing in commercial dental composites. Abstract: Objective: Fracture is one of the main causes for failure of resin-based composite restorations. To overcome this drawback, self-healing resin-based composites have been designed by incorporation of microcapsules. However, the relationship between their self-healing capacity and microcapsule and resin parameters is still poorly understood. Therefore, the objective of this study was to systematically investigate the effect of initiator concentration (in the resin) and microcapsule size and concentration on the self-healing performance of commercially available flowable resin-based composites. Methods: Poly(urea-formaldehyde) (PUF) microcapsules containing acrylic healing liquid were synthesized in small (33 ± 8 μm), medium (68 ± 21 μm) and large sizes (198 ± 43 μm) and characterized. Subsequently, these microcapsules were incorporated into a conventional flowable resin-based composite (Majesty Flow ES2, Kuraray) at different contents (5–15 wt%) and benzoyl peroxide (BPO) initiator concentrations (0.5–2.0 wt%). Fracture toughness ( K IC ) of test specimens was tested using a single edge V-notched beam method. Immediately after complete fracture ( K IC-initial ), the two fractured parts were held together for 72 h to allow for healing. Subsequently, fracture toughness of the healed resin-based composites ( K IC-healed ) was tested as well. Results: The fracture toughness of healed dental composites significantly increased with increasing microcapsule size and concentration (2 wt% BPO, p < 0.05). The highest self-healing efficiencies (up to 76%) were obtained with microcapsules sized 198 ± 43 um. Significance: commercially available resin-based composites can be rendered self-healing most efficiently by incorporation of large microcapsules (198 ± 43 μm). However, long-term tests on fatigue and wear behavior are needed to confirm the clinical efficacy.